2011
DOI: 10.4103/0019-5359.104783
|View full text |Cite
|
Sign up to set email alerts
|

Work related stress and its anticipated solutions among post-graduate medical resident doctors: A cross-sectional survey conducted at a tertiary municipal hospital in Mumbai, India

Abstract: There is a high level of work related stress among the resident doctors registered for postgraduate clinical studies at a tertiary Municipal hospital in Mumbai. One of the perceived stress busters is regular physical exercise that is structured and under supervision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 5 publications
(5 reference statements)
1
13
0
Order By: Relevance
“…43 Finally, a study involving Indian residents echoed these findings in identifying excessive clinical demands, poor onsite living facilities, not enough break time, a threat from deadly infections and an environment not conducive to clinical training as the greatest contributors to job-related stress. 44 These findings are all compatible with the 'demands' in Cox's balance model of stress, which suggests that acute stress occurs when demands on individuals outweigh their perceived control of the situation. 40 The latter study was the only one to identify strategies to reduce stress.…”
Section: Stress Managementsupporting
confidence: 61%
See 2 more Smart Citations
“…43 Finally, a study involving Indian residents echoed these findings in identifying excessive clinical demands, poor onsite living facilities, not enough break time, a threat from deadly infections and an environment not conducive to clinical training as the greatest contributors to job-related stress. 44 These findings are all compatible with the 'demands' in Cox's balance model of stress, which suggests that acute stress occurs when demands on individuals outweigh their perceived control of the situation. 40 The latter study was the only one to identify strategies to reduce stress.…”
Section: Stress Managementsupporting
confidence: 61%
“…Similarly, a study involving critical care nurses in South Africa identified the following stressors: patient complexity, demanding workload, role uncertainty, difficult intraprofessional relationships, poor communication, lack of sufficiently trained personnel, shift work and nurse migration . Finally, a study involving Indian residents echoed these findings in identifying excessive clinical demands, poor onsite living facilities, not enough break time, a threat from deadly infections and an environment not conducive to clinical training as the greatest contributors to job‐related stress . These findings are all compatible with the ‘demands’ in Cox's balance model of stress, which suggests that acute stress occurs when demands on individuals outweigh their perceived control of the situation .…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…In conformity to the current study, Swami found significant association of burnout with residents' workload which also was supported by Rajan. 17,20 However, Gander found long working hours and roster instability to be independently related to fatigue-related clinical errors; and sleepiness while driving. 21 In contrast to these findings, Shirom et al found that workload was the sole factor which mediated its effects through perceived stress on burnout.…”
Section: Determinants Of Burnoutmentioning
confidence: 99%
“…Most of the studies on quality of working conditions and work-life balance were conducted only among nurses in the healthcare industries and very few of them on doctors but none of the study included all the women staffs such as human resource (HR) women, hospital administrators (HA), secretaries, attenders, housekeeping women, doctors and nurses to the best of our knowledge. [5][6][7] With this background, the current study attempted to assess the working condition, balance of work and family life using work life conflict scale and also to establish the association of certain sociodemographic variables with work-life balance scores of married women working in tertiary care medical college hospital.…”
Section: Introductionmentioning
confidence: 99%